Graphene oxide Janus nanoplatelets of metal-polyphenol networks, and preparation method and application thereof
Patent Information
- Application Number
- CN202411735268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-29
Smart Images

Figure CN119551669B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of emulsion preparation technology, and in particular to a metal-polyphenol network graphene oxide Janus nanosheet, its preparation method and application. Background Technology
[0002] Plant-based essential oils (EOs) are important secondary products extracted from different parts of plants, mainly containing terpenes and phenolic compounds with broad-spectrum activity. Based on their broad-spectrum antioxidant, antibacterial, and nutritional benefits, EOs are widely used in pharmacology, medicine, and food. However, their inhibitory effects on plant pathogens are rarely studied. Currently, the reported antibacterial mechanism of EOs involves the active components disrupting the cell structure of fungi and generating reactive oxygen species to inhibit the growth and reproduction of pathogens. Therefore, EOs have potential application value in combating plant pathogens. It is well known that the use of chemical fungicides such as triazoles, methacrylates, and amides is a key means of preventing and controlling plant diseases caused by plant pathogens. However, the problems of drug resistance, biotoxicity, environmental pollution, and food safety associated with chemical fungicides are becoming increasingly serious. Studies have confirmed that EOs such as thymol, carvacrol, limonene, and eugenol have excellent comprehensive antibacterial properties, and fungi do not develop drug resistance. However, EOs are highly volatile at room temperature, poorly soluble in water, easily oxidized in air, and have a pungent odor. These drawbacks reduce the antibacterial properties of EOs and limit their application scenarios. Therefore, constructing a green and efficient EO encapsulation and release system is of great significance for expanding their practical applications.
[0003] Pickering emulsions are W / O or O / W emulsions formed using solid particles as emulsifiers. Compared to small-molecule surfactants and isotropic solid particles, two-dimensional Janus nanosheets (2D JNSs) exhibit superior emulsifying properties due to their high specific surface area, high anisotropy in structure and properties, and restricted interfacial rotation. Studies have shown that JNSs possess higher desorption energies at the oil-water interface, significantly enhancing the stability of oil emulsions and preventing leakage of encapsulated active substances. Currently, reported methods for preparing JNSs mainly include interfacial protection methods, phase separation methods, self-assembly methods, and template protection methods. However, these methods suffer from problems such as complex operation, the use of multiple initiators and organic solvents, limitations on monomer types, and low yields. Therefore, simple, universal, green, and mild preparation strategies for synthesizing functionalized JNSs are of great significance.
[0004] Graphene oxide (GO), a rigid hydrophilic 2D material, is covered with active functional groups including hydroxyl, carboxyl, and epoxy groups, making it an ideal template for the synthesis of chromogenic nanomaterials (JNSs). This method utilizes polyphenol monomers (tannic acid, dopamine, gallic acid, and epicatechin) with diverse structures, simple polymerization, and easy functionalization, along with metal ions (such as Cu). 2+ Fe 3+ Zn 2+ Ti 4+ By complexing with other molecules (such as polyphenols) to form functionalized metal-polyphenol networks (MPNs) on the GO surface, metal-polyphenol network GO JNSs can be prepared. This material combines the advantages of JNSs and MPNs, endowing Pickering emulsions with specific functions such as enhanced emulsion stability, interfacial adhesion, UV resistance, antioxidant properties, and synergistic antibacterial activity, providing an ideal carrier for the encapsulation, release, and enhanced antibacterial activity of EOs. Summary of the Invention
[0005] The purpose of this invention is to provide a metal-polyphenol network graphene oxide (JANUS) nanosheet, its preparation method, and its applications. Based on a thorough understanding of JNSs synthesis, EOs picking emulsion preparation methods, and the antibacterial mechanism of EOs, a template protection method is proposed to prepare a metal-polyphenol network GO JNSs and use it to form an EOs picking emulsion for the prevention and control of plant diseases. Using GO JNSs as a solid emulsifier to encapsulate EOs can solve the problems of EOs' easy volatility and poor water solubility at room temperature, while also achieving synergistic antibacterial effects with adjuvants in the system.
[0006] The solution of the present invention is:
[0007] A metal-polyphenol network graphene oxide Janus nanosheet includes hydrophobic units provided by a solid template and hydrophilic units provided by a metal-polyphenol network coating; the metal-polyphenol network graphene oxide Janus nanosheet is obtained by metal-polyphenol modification after solid template protection.
[0008] As a preferred technical solution, the solid template is polystyrene (PS), amino-modified polystyrene (NH2-PS), polymethyl methacrylate (PMMA), or solid paraffin, with NH2-PS being a more preferred template.
[0009] When modifying the outer side of GO with a metal-polyphenol network, the polyphenol monomer can be tannic acid (TA), dopamine, gallic acid and epicatechin, and more preferably tannic acid (TA).
[0010] The metal is Cu 2+ Fe 3+ Zn 2+ Ti4+ One of them, more preferably Ti 4+ (Di(2-hydroxypropionic acid)diammonium hydroxide titanium, Ti-BALDH).
[0011] As a preferred technical solution, the graphene oxide Janus nanosheets of the metal-polyphenol network have a sheet diameter in the micrometer range and a thickness of 4.5 nm as measured by AFM; the graphene oxide Janus nanosheets of the metal-polyphenol network are TA-Ti / GO / NH2-PS nanosheets, including hydrophilic units provided by TA-Ti and hydrophobic units provided by NH2-PS.
[0012] The TA-Ti / GO / NH2-PS nanosheets were obtained by modifying graphene oxide with NH2-PS as a template using TA-Ti.
[0013] The present invention also discloses a method for preparing graphene oxide Janus nanosheets of a metal-polyphenol network, comprising the following steps: in a mixed solution, graphene oxide and NH2-PS are electrostatically adsorbed, a metal-polyphenol network coating is applied to the outer side, and the template is washed away to obtain the graphene oxide Janus nanosheets of the metal-polyphenol network, wherein the mixed solution is a mixture of ethanol and water.
[0014] As a preferred technical solution, the following steps are included:
[0015] S1. Graphene oxide and a solid template are bonded through non-covalent interactions. A solid template with a diameter of 1 μm is dispersed in a mixture, graphene oxide is added, and the mixture is stirred at a speed of 500-800 rpm to allow the graphene oxide to be adsorbed onto the solid template. The volume ratio of ethanol to water in the mixture is 1:1-3.
[0016] S2. Modification of the metal-polyphenol network coating: Polyphenol and metal are added to the product obtained in step S1 and dispersed in a mixed solvent of Tirs-HCl buffer and water. The mixture is stirred at a speed of 500-800 rpm for 10-60 min to obtain microspheres with a metal-polyphenol network coating on the outside of the nanosheets.
[0017] S3. Use an organic solvent to etch the microspheres obtained in step S2 to obtain graphene oxide Janus nanosheets of a metal-polyphenol network; the organic reagent is one of n-hexane, ethyl acetate, dichloromethane and tetrahydrofuran.
[0018] As a preferred technical solution, the following steps are also included:
[0019] S1 also includes the purification of NH2-PS@GO. After the reaction in step S1 is completed, the reaction solution in step S1 is washed and centrifuged multiple times with a mixture to remove unreacted graphene oxide and NH2-PS. The obtained solid is placed in a vacuum drying oven at 40-60°C and dried for 6-8 hours.
[0020] S3 also includes the purification of GO JNSs. After the reaction in step S3 is completed, the reaction solution in step 3 is washed and centrifuged multiple times with the mixed solution to remove the solid template. The precipitate that is finally centrifuged is washed and filtered with the mixed solution. The obtained solid is placed in a vacuum drying oven at 40-60℃ and dried for 6-12 hours to obtain the graphene oxide Janus nanosheets of the metal-polyphenol network.
[0021] As a preferred technical solution, the mixture is ethanol and water, with a volume ratio of ethanol to water of 1:2; the stirring speed in step S1 is 600-700 rpm.
[0022] The modification of the metal-polyphenol network coating is as follows: S1, TA and Ti-BALDH are added to the prepared template, with a molar ratio of TA to Ti-BALDH of 1:1 to 3, more preferably 1:1; S2, the stirring speed is 600-700 rpm; the reaction is carried out under weakly alkaline conditions for 15-30 min.
[0023] In step S3, the sample is washed with anhydrous ethanol and centrifuged, and the process is repeated 3-4 times. The resulting solid is then placed in a vacuum drying oven at 50-60℃ for 6-8 hours. The final product is TA-Ti / GO / NH2-PS JNSs.
[0024] The present invention also discloses an emulsifier, which is a metal-polyphenol network of graphene oxide Janus nanosheets.
[0025] The present invention also discloses a plant essential oil Pickering emulsion, which is formed by using graphene oxide Janus nanosheets of a metal-polyphenol network as an emulsifier.
[0026] As a preferred technical solution, the Pickering emulsion is an oil-in-water emulsion; in the Pickering emulsion, the volume ratio of the oil phase to the water phase is 1-10:90-99; in the Pickering emulsion, the concentration of graphene oxide Janus nanosheets of the metal-polyphenol network is 0.5-4 mg / mL.
[0027] The Pickering emulsion is obtained by dispersing the graphene oxide Janus nanosheets of the metal-polyphenol network of claim 1 into an aqueous phase, adding an auxiliary agent, and then mixing and emulsifying it with an oil phase.
[0028] The oil phase is one or more of the following natural plant essential oils: citronella oil, thymol, carvacrol, turpentine oil, and eugenol; the pH of the aqueous phase is 1-12.
[0029] The additive is one or more of chitosan, quaternized chitosan, chitin and gum arabic;
[0030] The pH stability of the Pickering emulsion is 3–11.
[0031] As a preferred technical solution, the EOs Pickering emulsion formed using TA-Ti / GO / NH2-PS JNSs is of the O / W type, and the concentration of JNSs is 1.0-2.0 mg / mL.
[0032] As a preferred technical solution, the oil phase is turpentine oil and eugenol (EU).
[0033] As a preferred technical solution, the additive is quaternized chitosan (QCS). The mass fraction of QCS is 0.25wt%-1wt%, and more preferably 0.75wt%-1wt%.
[0034] As a preferred technical solution, citric acid and NaOH are selected as pH adjusters.
[0035] As a preferred technical solution, the pH of the Pickering emulsion is 7 as the emulsion preparation condition.
[0036] This invention also discloses the application of a plant essential oil Pickering emulsion for the prevention and control of fungal diseases caused by foliar fungi on plants. The fungal disease is tomato gray mold.
[0037] As a preferred technical solution, JNSs-EU-PE was diluted 1-200 times and added to PDA medium, and then inoculated with Botrytis cinerea Pers. Fr. to study the antibacterial effect of the JNSs-EU-PE concentration gradient on B. cinerea. The lowest effective inhibitory concentration was used to address plant diseases caused by foliar fungi in the agricultural field.
[0038] Janus nanosheets of graphene oxide, which employ a metal-polyphenol network, are prepared and applied, including hydrophobic units provided by a solid template and hydrophilic units provided by a metal-polyphenol network coating. The graphene Janus nanosheets of the metal-polyphenol network are obtained by metal-polyphenol modification after solid template protection.
[0039] Advantages of this invention:
[0040] This invention employs a template protection method to modify the outer surface of GO nanosheets with a metal-polyphenol network (MPNs). After template etching, the inner surface is composed of hydrophobic NH2-PS, and the outer surface is composed of hydrophilic MPNs. The polyphenols impart excellent interfacial adhesion to the nanosheets, firmly anchoring the GO JNSs at the interface. Introducing metal ions to complex with the polyphenols reduces polyphenol aggregation, thereby obtaining a uniform hydrophilic MPN layer. Simultaneously, the antibacterial properties of the MPNs synergistically enhance the antibacterial effect with EOs.
[0041] Compared to small molecule surfactants, which suffer from drawbacks such as high dosage, poor stability, and lack of functionality, the metal-polyphenol network GO JNSs prepared in this invention exhibits excellent amphiphilic properties, requires a low emulsifier concentration to form stable Pickering emulsions, produces uniform droplets with a particle size of less than 10 μm, and demonstrates faster migration rates at the interface. The modified polyphenol-metal network structure endows GO JNSs with beneficial effects such as interfacial adhesion, UV protection, antioxidant properties, and synergistic antibacterial activity.
[0042] Commercially available fungicides require large dosages, have limited antibacterial properties, easily lead to drug resistance in plant pathogens, and pose a threat to human safety when left in the environment. However, endogenous phosphoric acid (EOs), as important secondary metabolites extracted from plants, are widely available, environmentally friendly, and have no phytotoxic effects. Using EOs as the oil phase to form a Pickering emulsion fully leverages their broad-spectrum antibacterial properties and solves the problems of EOs' volatility at room temperature, poor water solubility, easy oxidation, and pungent odor. The EOs-Pickering emulsion formed by this invention exhibits good stability at pH 3-11, which greatly expands the application scenarios of the emulsion—an effect that small molecule surfactants cannot achieve. Furthermore, the metal-polyphenol network GO JNSs adsorbed on the EOs surface firmly "anchors" to the EOs-water interface through non-covalent interactions between polyphenols, between polyphenols and EOs, and between polyphenols and other additives (such as QCS), achieving stable encapsulation and release of EOs. Attached Figure Description
[0043] Figure 1 This is a flowchart illustrating the preparation process of TA-Ti / GO / NH2-PS JNSs and JNSs-EU-PE in this invention.
[0044] Figure 2 The images shown are electron scanning images of TA-Ti / GO / NH2-PS JNSs in Embodiment 5 of the present invention, where a is a SEM image, b is a TEM image, and c is an AFM image.
[0045] Figure 3 This is a diagram showing the water contact angles on both sides of the TA-Ti / GO / NH2-PS JNSs in Embodiment 5 of the present invention;
[0046] Figure 4The images show the bouncing behavior of test 1 of this invention; where a represents the bouncing behavior of water, TW-80-EU-E, JNSs-EU-PE, and EU-EW on a hydrophobic paraffin layer, and the normalized droplet height b and normalized diameter c change with time; d represents the bouncing behavior of water, TW-80-EU-E, JNSs-EU-PE, and EU-EW on tomato leaves at 0°, 30°, and 60°.
[0047] Figure 5 This is a comparative diagram of the components in Test 2 of this invention on tomato leaves; where a represents the adhesion process of water, TW-80-EU-E, JNSs-EU-PE, and EU-EW on tomato leaves; b represents the relationship between droplet position and weight; c represents the breakup distance and residual mass of different droplets; d represents the contact angle and deposition amount of water, TW-80-EU-E, JNSs-EU-PE, and EU-EW on tomato leaves; e represents the Nile Red-labeled EU, CLSM images of tomato leaves before and after water washing, scale bar: 10 μm;
[0048] Figure 6 This is a comparison of the moisture retention performance and absorption efficiency of tomato leaves in Test Example 3 of the present invention. In a, a is a SEM image of TW-80-EU-E, JNSs-EU-PE and EU-EW deposited on tomato leaves at 0h and 12h, scale bar: 50μm; b is a photograph of the residual droplets of JNSs-EU-PE and EU-EW on tomato leaves; c is the change of leaf mass loss over time after treatment with JNSs-EU-PE and EU-EW; d is a CLSM image of tomato roots, stems and leaves after Nile Red-labeled EU treatment, scale bar: 100μm.
[0049] Figure 7 The figures shown are the test results of Test 4 in this invention; where a is a photograph of the anti-gray mold plate experiment of QCS and JNSs; b is the in vitro antibacterial activity of QCS and JNSs; c is a photograph of the anti-gray mold plate experiment of TW-80-EU-E, JNSs-EU-PE and EU-EW; d is the in vitro antibacterial activity of TW-80-EU-E, JNSs-EU-PE and EU-EW; and e is the EC50 of TW-80-EU-E, JNSs-EU-PE and EU-EW. 50 f is a SEM image of gray mold mycelium after normal growth, scale bar: 50 μm; g is a SEM image of gray mold mycelium after JNSs-EU-PE treatment, scale bar: 50 μm; h is a CLSM image of gray mold before and after Nile Red-labeled EU treatment, scale bar: 10 μm;
[0050] Figure 8The images show the comparative effects of the antibacterial effects of the five emulsions tested in this invention; where a is a photograph of the growth of gray mold on tomato fruits treated with TW-80-EU-E, JNSs-EU-PE, EU-EW, and BSC-PMT-SC within 4 days; b is the area of tomato lesions after treatment with TW-80-EU-E, JNSs-EU-PE, EU-EW, and BSC-PMT-SC; and c is the inhibition rate of gray mold growth after treatment with TW-80-EU-E, JNSs-EU-PE, EU-EW, and BSC-PMT-SC.
[0051] Figure 9 Photos of gray mold growth on tomato leaves treated with TW-80-EU-E, JNSs-EU-PE, EU-EW and BSC-PMT-SC in this invention over 4 days.
[0052] Figure 10 This is a comparison chart of the cytotoxicity tests conducted in this invention, including the relative cell viability after 24 hours of treatment of L0-2 cells with JNSs-EU-PE and EU-EW. Detailed Implementation
[0053] To make the technical means, creative features, objectives and effects of this invention easier to understand, the invention will be further described below with reference to specific embodiments.
[0054] The following embodiments are only for further detailed description of the present invention, but do not constitute any limitation on the present invention; the materials used in the following embodiments, unless otherwise specified, were purchased from conventional chemical reagent companies and raw material suppliers.
[0055] Example 1:
[0056] like Figure 1 As shown, the process flow is used to prepare TA-Ti / GO / NH2-PS JNSs.
[0057] First, measure 20 mL of GO nanosheet aqueous dispersion into a beaker and dilute with deionized water. Weigh NH2-PS microspheres and disperse them in anhydrous ethanol.
[0058] The second step involves adding an ethanol solution containing NH2-PS microspheres to a GO aqueous solution, with a stirring speed of 700 rpm and a stirring time of 12 hours.
[0059] The third step is to centrifuge at 10,000 rpm for 3 minutes after the reaction is complete, and wash with anhydrous ethanol and water. Repeat this process 3-5 times, and then place the obtained solid in a vacuum drying oven at 60℃ for 6-8 hours.
[0060] Example 2:
[0061] The preparation method is the same as in Example 1, except that NH2-PS microspheres are replaced with PS microspheres.
[0062] Example 3:
[0063] The preparation method is the same as in Example 1, except that NH2-PS microspheres are replaced with PMMA microspheres.
[0064] Example 4:
[0065] The first step is to prepare an aqueous dispersion of GO by adding solid paraffin (melting point 54-56℃), heating it above the melting point of the solid paraffin, emulsifying it, and then allowing it to cool naturally to room temperature.
[0066] Example 5:
[0067] The first step is to weigh the solid product from Example 1 and add it to deionized water for ultrasonic dispersion.
[0068] The second step involves adding TA to Ti-BALDH in a 3:1 mass ratio to a round-bottom flask. Tirs-HCl buffer is added to control the pH of the solution to 8.5. The stirring speed is 700 rpm, and the reaction time is 30 minutes.
[0069] The third step is to centrifuge at 8000 rpm for 3 minutes after the reaction is complete, and wash with anhydrous ethanol and water. Repeat this process 3-5 times.
[0070] Fourth step: Add a mixture of THF and water (v / v, 10:1) to the product from the previous step and then subject it to ultrasonic etching. Centrifuge at 10,000 rpm for 3 min and wash with anhydrous ethanol, repeating the cycle 3-5 times. Dry in a vacuum oven at 60℃ for 6 h to finally obtain TA-Ti / GO / NH2-PS JNSs.
[0071] Comparative Example 5-1:
[0072] The preparation method is the same as in Example 5, except that only TA is added and Ti-BALDH is not added.
[0073] Comparative Example 5-2:
[0074] The preparation method is the same as in Example 5, except that the polyphenol monomer is replaced with dopamine hydrochloride.
[0075] Comparative Example 5-3:
[0076] The preparation method is the same as in Example 5, except that Ti-BALDH is replaced with TiCl3.
[0077] Comparing Example 5, Comparative Example 5-1, and Comparative Example 5-2, the coordination between the metal and polyphenol in Example 5 resulted in a more uniform and smooth coating, and the use of TA as the polyphenol monomer yielded even better results. Figure 2 (a) It can be seen that the morphologies on both sides of TA-Ti / GO / NH2-PS JNSs are different, with the metal-polyphenol network side being relatively rough and the NH2-PS-containing side being relatively smooth. Figure 2 (b) is the TEM image of TA-Ti / GO / NH2-PS JNSs. AFM testing shows that the prepared nanosheet thickness of 4.5 nm is significantly different from the original GO thickness of 1.5 nm. TA-Ti / GO / NH2-PS JNSs films were prepared by utilizing the self-assembly behavior exhibited by TA-Ti / GO / NH2-PS JNSs at the oil-water interface. Figure 3 The static water contact angles on both sides of the membrane were 76.70° and 117.37°, respectively, indicating that the TA-Ti / GO / NH2-PS JNSs prepared in Example 5 have amphiphilic properties.
[0078] Example 6:
[0079] Preparation of eugenol (EU) Pickering emulsion.
[0080] The first step was to disperse the TA-Ti / GO / NH2-PS JNSs obtained in Example 5 in deionized water at a concentration of 1 mg / mL.
[0081] The second step involves transferring 7.5% EU by volume into a screw-top bottle, adding 0.75 wt% QCS, and ultrasonically emulsifying to obtain an O / W EU Pickering emulsion (JNSs-EU-PE).
[0082] Comparative Example 6-1:
[0083] Equal mass fractions of TW-80 aqueous solution and EU (volume fraction 7.5%) were mixed and ultrasonically emulsified to obtain EU emulsion (TW-80-EU-E).
[0084] Comparative Example 6-2:
[0085] The commercially available 20% EU emulsion was diluted with deionized water, with the effective concentration of EU being the same as in Example 5. The resulting sample was called EU EW.
[0086] Example 7:
[0087] Following the emulsion preparation process in Example 6, the pH of the aqueous phase was changed (pH = 3-11).
[0088] Example 8:
[0089] Following the emulsion preparation process in Example 6, the concentration of JNSs was varied to 0.3, 0.5, 0.7, and 1.0 (mg / mL).
[0090] Example 9:
[0091] Following the emulsion preparation process in Example 6, the EU volume fraction was varied (2.5%, 5%, 7.5%, 10%).
[0092] Example 10:
[0093] Following the emulsion preparation process in Example 6, the EU volume fraction was determined to be 7.5%, and the QCS mass fraction was changed to 0.25, 0.5, 0.75, and 1.0 (wt%).
[0094] Test Example 1
[0095] The bouncing behavior of EU emulsion on hydrophobic paraffin layers and tomato leaves was evaluated.
[0096] Test method: Take pictures using a high-speed camera.
[0097] Test procedure: The samples from Example 6 and Comparative Examples 6-1 to 6-2 were diluted 100 times, and the bouncing behavior of the diluted solutions on a clean hydrophobic paraffin layer and tomato leaves was studied using a high-speed camera.
[0098] Depend on Figure 4 As shown in (ac), deionized water completely rebounds on the hydrophobic paraffin layer, exhibiting the smallest maximum spreading diameter. The rebound height of JNSs-EU-PE on the hydrophobic paraffin layer is lower than that of the emulsion formed by the small molecule surfactant TW-80, and its maximum spreading diameter is larger than that of commercially available EU water-based emulsions, demonstrating that JNSs-EU-PE possesses excellent wetting and spreading capabilities. Figure 4 (d) It is evident that deionized water, TW-80-EU-E, and EU-EW all exhibited varying degrees of bouncing and splashing during contact with tilted tomato leaves, resulting in significant loss of active ingredients. JNSs-EU-PE, due to its combination of polyphenol adhesion, low interfacial free energy of the emulsion system, and hydrogen bonding interaction with the leaf surface, demonstrated significantly superior wetting and spreading ability compared to TW-80-EU-E. On tilted leaves, the rebound and rolling effects of JNSs-EU-PE were far weaker than those of TW-80-EU-E and EU-EW. This is attributed to the relative sliding of JNSs on the leaves under the influence of gravity, enabling it to continuously modify the leaves over a larger area.
[0099] Test Example 2
[0100] The adhesion, deposition, and resistance to rain washout of different emulsions on tomato leaves were evaluated.
[0101] Testing Procedure: During the application of pesticide emulsions, factors such as droplet misalignment and splashing on the leaf surface can affect the actual effectiveness of the pesticide. Adhesion tests on the droplets on the leaves can evaluate the rapid wetting and spreading ability of the droplets after contact with the leaf surface. After contact with the leaf surface, the droplets are affected by gravity, causing a large number of droplets to detach from the leaf surface. The Wilhelmy method is used to determine the final deposition amount of droplets under the influence of gravity. After pesticides are deposited on the leaf surface, the active ingredients are washed away by rainwater and enter the soil, resulting in low application efficiency and environmental pollution. Fluorescent labeling of the pesticide is used to simulate rainwater washing away from the leaves after pesticide application. The changes in fluorescence intensity are used to evaluate the pesticide's resistance to rainwater washing away.
[0102] Tomato leaves were fixed on a glass slide, and the adhesion test mode of a surface tension meter was used. Each test was conducted by hanging the same volume of droplets on the ring.
[0103] Depend on Figure 5 (a) It can be seen that the spreading effect of JNSs-EU-PE on tomato leaves is between that of TW-80-EU-E and EU-EW. Figure 5 As shown in (bc) (the horizontal axis represents the distance from the droplet to the leaf surface, and the vertical axis represents the residual mass and breakup distance of the droplet on the ring), it can be seen that the breakup distance of JNSs-EU-PE on the leaf surface is shorter than that of TW-80-EU-E, and the residual amount of JNSs-EU-PE on the leaf surface is 0.008g, which is higher than other emulsions. A shorter breakup distance indicates a stronger wetting and spreading ability of the droplet on the leaf surface, which is more conducive to droplet deposition during application. A larger residual amount of droplet on the leaf is more conducive to achieving the purpose of pesticide use. Figure 5 (d) Based on the leaf surface deposition and contact angle experiments of the emulsion, it was demonstrated that JNSs-EU-PE can rapidly wet the hydrophobic surface (123.71°) (70.74°) after leaf surface contact, and the deposition amount can reach 18 mg / cm³ after the influence of gravity. 2 This is mainly because the polyphenolic side of JNSs possesses excellent adhesion and hydrophilicity, ensuring the emulsion can rapidly wet and spread on the leaf surface. The network structure composed of multiple non-covalent interactions in JNSs-EU-PE weakens the effects of gravity. Rain erosion resistance experiments were conducted after fluorescently labeling the oil phase, such as... Figure 5 As shown in (e), the residual fluorescence intensity of JNSs-EU-PE is higher than that of other emulsions, further demonstrating the excellent leaf adhesion effect of JNSs-EU-PE.
[0104] Test Example 3
[0105] Investigating the moisturizing properties and absorption efficiency of the emulsion on tomato leaves.
[0106] Test Procedure: Samples from Example 6, Comparative Example 6-1, and Comparative Example 6-2 were diluted to ensure consistent EU concentrations. The diluted samples were sprayed onto tomato leaves, and the leaf morphology was observed using SEM at 0 h and 12 h after spraying. Leaves of uniform size were selected, and an equal volume of emulsion was sprayed onto the leaf surface. Leaf mass was measured at fixed intervals. After labeling EU with Nile Red, TW-80-EU and JNSs-EU-PE were sprayed onto tomato leaves, and fluorescence imaging of tomato leaves, stems, and roots was performed 12 h later.
[0107] from Figure 6 (a) After 12 hours of observation, TW-80-EU and EU-EW droplets were relatively dispersed on the leaves. The non-covalent interactions present in JNSs-EU-PE induced a dense network structure of droplets on the leaf surface, forming a surface film that sealed the leaves. Leaf moisture retention experiment ( Figure 6 (b) and (c) show that after 95 min, EU-EW was completely dry on the leaf surface, but JNSs-EU-PE still remained, with a 12.26% higher residue than EU-EW. Figure 6 (d) shows that after 12 h, the fluorescent signal of the JNSs-EU-PE label appeared in the stems and roots. This is attributed to the "moisturizing" and "sealing effect" facilitating the internal transport of the emulsion.
[0108] Test Example 4
[0109] The inhibition zone experiment was conducted on different emulsions to investigate their inhibitory effect on botrytis cinerea in tomatoes and to provide a reference for subsequent experiments on detached leaves and fruits.
[0110] Test Procedure: Samples from Example 6, Comparative Example 6-1, and Comparative Example 6-2 were diluted and added to PDA medium according to the EU concentration gradient for incubation. The diameter of the bacterial pellet was measured. The inhibition rate was calculated according to the following formula, and the half-maximal effective concentration (EC50) of the emulsion was analyzed using SPSS software. 50 ).
[0111]
[0112] Figure 7 (ab) shows the antibacterial test results of QCS and JNSs plates. The experiment proved that both QCS and JNSs have antibacterial properties, with JNSs having an inhibition rate of 22.54% and QCS having an inhibition rate of 8.92%. Figure 7 (c) Plate antibacterial experiments of Example 6, Comparative Example 6-1 and Comparative Example 6-2. It can be seen from the figure that when the EU concentration reaches 0.8 mg / mL, both JNSs-EU-PE and EU-EW show complete inhibition of Botrytis cinerea growth. Figure 7In (d), when the EU concentration was below 0.08 mg / mL, the antibacterial effect of JNSs-EU-PE was superior to other emulsions, which is related to the synergistic antibacterial ability of QCS and JNSs in the emulsion. Figure 7 (e) Obtain EC 50 JNSs-EU-PE's EC 50 The concentration of 0.235 mg / mL falls between that of TW-80-EU-E (0.507 mg / mL) and EU-EW (0.169 mg / mL), indicating that its antibacterial activity is superior to that of emulsions formed by surfactants. Figure 6 (fg) shows SEM images of *Botrytis cinerea* under normal growth and after treatment with JNSs-EU-PE. It can be seen that the surface morphology of the hyphae changed from rough to relatively smooth after treatment with JNSs-EU-PE. This demonstrates that JNSs-EU-PE achieves its antibacterial effect by disrupting the biological barrier of *Botrytis cinerea* hyphae. EU was labeled with Nile Red, and images were obtained using laser confocal microscopy (CLSM). Figure 6 (h) JNSs-EU-PE can penetrate the biological barrier of gray mold hyphae and enter the hyphae.
[0113] Test Example 5
[0114] Test Example 4 determined that an emulsion with an EU concentration of 0.8 mg / mL was used to conduct an anti-gray mold experiment on tomato fruits to evaluate the antibacterial effect of each emulsion in a real-world scenario.
[0115] Test Procedure: Several tomatoes of suitable size were selected, sprayed with the fungicide solution, and inoculated with 7mm diameter gray mold. The inoculated tomatoes were then placed in an artificial climate chamber with humidity above 90% and a constant temperature of 25±3℃. Disease incidence was recorded the following day. The preventive effect of different latexes on gray mold infection of tomato fruits was calculated using the inhibition rate formula.
[0116]
[0117] Take photos of the tomato disease symptoms for four consecutive days, such as... Figure 8 As shown in (a), JNSs EU PE patients exhibited the mildest symptoms after four days of infection. Figure 8 (b) The lesion area was statistically analyzed; the lesion area on the fourth day of JNSs-EU-PE was 6.52 cm². 2 It was lower than that of other treatment groups. Figure 8 (c) The inhibition rate obtained by the conversion of lesion area. The inhibitory effect of JNSs-EU-PE on tomato fruit infected with gray mold within four days (31.14%) is comparable to that of commercially available water emulsion (27.20%) and the current mainstream chemical synthetic pesticide for controlling gray mold (pyrimethanil-pyrimethanil suspension, BSC-PMT-SC, 28.50%).
[0118] Test Example 6
[0119] In vitro leaf experiments were conducted using various emulsions with an EU concentration of 0.8 mg / mL.
[0120] Test process: Select healthy, uniformly sized tomato leaves, spray them with pesticide solution, inoculate them with gray mold with a diameter of 7mm, and place the inoculated leaves in a constant temperature artificial climate chamber with humidity above 90% and temperature of 25±3℃ for four consecutive days to take photos of the diseased leaves.
[0121] The disease incidence of tomato leaves is shown in Figure (9). After four days of statistical analysis, it was found that the leaves treated with JNSs-EU-PE had the mildest disease symptoms.
[0122] Experiments on tomato fruits and detached leaves demonstrated the feasibility of using JNSs-EU-PE, formed with GO JNSs as a solid emulsifier and plant essential oils as a natural antibacterial agent, as a surfactant-free, green, and highly effective bactericide.
[0123] Test Example 7
[0124] Cytotoxicity assays were performed using JNSs-EU-PE and EU-EW at EU concentration gradients.
[0125] Test Procedure: Logarithmic growth phase human hepatocytes (L0-2) were seeded into 96-well plates. After cell adhesion, the culture medium was discarded, and medium containing JNSs-EU-PE or EU-EW was added to each well, with EU concentrations of 0.01, 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8 mg / mL, respectively. Cells were incubated at 37℃ in a 5% CO2 incubator for 24 h. After adding thiazolyl blue (MTT) for culturing, the crystals were dissolved using dimethyl sulfoxide (DMSO), and the absorbance at 490 nm was measured using a multi-mode microplate reader to determine the relative viability of L0-2 cells in different treatment groups.
[0126] After 24 hours of culture, the cell viability of JNSs-EU-PE and EU-EW under EU concentration gradients is shown in Figure (10). The cell viability of JNSs-EU-PE was higher than that of EU-EW at EU concentrations of 0.01, 0.05, 0.1, 0.2, 0.4, 0.6, and 0.8 mg / mL. At the EU antibacterial concentration used (0.8 mg / mL), the cell viability of JNSs-EU-PE was 55.65%, higher than that of EU-PE (26.47%). Cytotoxicity experiments demonstrated that JNSs-EU-PE poses less harm to humans and is safer than commercially available water-based emulsions.
[0127] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A metal-polyphenol network graphene oxide Janus nanosheet, characterized in that: It includes hydrophobic units provided by a solid template and hydrophilic units provided by a metal-polyphenol network coating; the graphene oxide Janus nanosheets of the metal-polyphenol network are obtained by metal-polyphenol modification after solid template protection; The polyphenols in the metal-polyphenol network coating are one or more of tannic acid, dopamine, gallic acid, and epicatechin, and the metal is Cu. 2+ Fe 3+ Zn 2+ Ti 4+ One or more of the following; The solid template is one or more of PS, NH2-PS, PMMA, and solid paraffin.
2. The metal-polyphenol network graphene oxide Janus nanosheet as described in claim 1, characterized in that: The graphene oxide Janus nanosheets of the metal-polyphenol network have a sheet diameter in the micrometer range; the graphene oxide Janus nanosheets of the metal-polyphenol network are TA-Ti / GO / NH2-PS nanosheets, including hydrophilic units provided by TA-Ti and hydrophobic units provided by NH2-PS. The TA-Ti / GO / NH2-PS nanosheets were obtained by modifying graphene oxide with NH2-PS as a template using TA-Ti.
3. A method for preparing graphene oxide Janus nanosheets with a metal-polyphenol network as described in any one of claims 1 or 2, characterized in that, The process includes the following steps: in a mixture, graphene oxide and NH2-PS are electrostatically adsorbed, a metal-polyphenol network coating is applied to the outside, and the template is washed away to obtain the graphene oxide Janus nanosheets of the metal-polyphenol network. The mixture is a mixture of ethanol and water.
4. The method for preparing metal-polyphenol network graphene oxide Janus nanosheets as described in claim 3, characterized in that, Includes the following steps: First, measure 20 mL of GO nanosheet aqueous dispersion into a beaker and dilute with deionized water. Weigh NH2-PS microspheres and disperse them in anhydrous ethanol. The second step involves adding an ethanol solution containing NH2-PS microspheres to a GO aqueous solution, with a stirring speed of 700 rpm and a stirring time of 12 h. The third step is to centrifuge at 10,000 rpm for 3 min after the reaction is complete and wash with anhydrous ethanol and water. Repeat this cycle 3-5 times and place the obtained solid in a vacuum drying oven at 60 ℃ for 6-8 h. Fourth step: Weigh the solid product from the third step and add it to deionized water for ultrasonic dispersion; Step 5: Add TA to Ti-BALDH in a round-bottom flask at a mass ratio of 3:1; add Tirs-HCl buffer to control the pH of the solution to 8.5; stir at 700 rpm for 30 min. Step 6: After the reaction is complete, centrifuge at 8000 rpm for 3 min and wash with anhydrous ethanol and water. Repeat this process 3-5 times. Step 7: Add a mixture of THF and water to the product from the previous step and place it in an ultrasonic etching chamber. The volume ratio of THF to water is 10:
1. Centrifuge at 10,000 rpm for 3 min and wash with anhydrous ethanol. Repeat the cycle 3-5 times. Dry in a vacuum oven at 60 ℃ for 6 h to finally obtain TA-Ti / GO / NH2-PS JNSs.
5. The method for preparing metal-polyphenol network graphene oxide Janus nanosheets as described in claim 4, characterized in that: The NH2-PS microspheres are replaced with either PS microspheres or PMMA microspheres.
6. An emulsifier, characterized in that: The emulsifier is Janus nanosheets of graphene oxide from the metal-polyphenol network described in claim 1.
7. A plant essential oil Pickering emulsion, characterized in that: Pickering emulsions are formed using Janus nanosheets of graphene oxide from the metal-polyphenol network of claim 1 or claim 6 as emulsifiers.
8. A plant essential oil Pickering emulsion as described in claim 7, characterized in that: The Pickering emulsion is an oil-in-water emulsion; in the Pickering emulsion, the volume ratio of the oil phase to the water phase is 1-10:90-99; in the Pickering emulsion, the concentration of graphene oxide Janus nanosheets of the metal-polyphenol network is 0.5-4 mg / mL. The Pickering emulsion is obtained by dispersing the graphene oxide Janus nanosheets of the metal-polyphenol network of claim 1 into an aqueous phase, adding an auxiliary agent, and then mixing and emulsifying it with an oil phase. The oil phase is one or more of the following natural plant essential oils: citronella oil, thymol, carvacrol, turpentine oil, and eugenol; the pH of the aqueous phase is 1-12. The additive is one or more of chitosan, quaternized chitosan, chitin and gum arabic; The pH stability of the Pickering emulsion is 3–11.
9. The use of the Pickering emulsion of plant essential oil as described in any one of claims 7 or 8 in the prevention and control of gray mold in plants.
Citation Information
Patent Citations
Oxidized graphene / waterborne polyurethane acrylate composite emulsion and preparation method and application thereof
CN106632878A
Functional reduced graphene oxide / metal-polyphenol framework composite aerogel wave-absorbing material and preparation method thereof
CN117998830A